The Influence Of Product Completeness And Price On The Purchasing Decisions Of Motorcycle Spare Parts At Nica Motor Kepahiang - Refaldo Rolansya; Ida Anggriani; Nenden Restu Hidayah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Each varied product and affordable prices will provide a distinct advantage for companies engaged in the trading sector because this will provide an incentive for consumers to take an action to purchase at the company. The purpose of this research is to determine the effect of product completeness and price on the decision to purchase spare parts at Nica Motor Kepahiang. The samples in this study were 60 respondents according to the minimum sample. Data were collected using a questionnaire and analyzed through multiple linear regression, determination test and hypothesis testing. From the calculation of the multiple linear regression equation, it can be seen that X1 (product completeness) and X2 (price) have an influence on purchasing decisions (Y), with the results of the regression test: Y = 9.920 + 0.304X1 + 0.455 X2.. The value of the coefficient of determination is 0.498. This means that product completeness (X1) and price (X2) affect the purchasing decisions (Y) by 49.8% while the rest (100 - 49.8 = 50.2%) are influenced by other variables not examined in this study. The results of the partial hypothesis test for variable X1 (product completeness) show that tcount is greater than ttable (2.797 > 1.671) and a significance value of 0.007 <0.05, then H0 is rejected and Ha is accepted. This means that X1 (product completeness) has a significant influence on purchasing decisions (Y). Variable X2 (price) shows that tcount is greater than ttable (4.479 > 1.671) and a significance value of 0.007<0.05, then H0 is rejected and Ha is accepted. This means that X2 (price) has a significant influence on purchasing decisions (Y). The simultaneous hypothesis test results show that the value of Fcount > Ftable (28.316 > 3.16) is in line with a significance of 0.000 <0.05. meaning that together product completeness (X1) and price (X2) have a positive and significant influence on purchasing decisions (Y).